Postoperative complications following simultaneous therapeutic and contralateral prophylactic nipple-sparing mastectomy: a retrospective study - Sonagli, Marina; Bertolli, Eduardo; Dutra, Alexandre Katalinic; Iyeyasu, Hirofumi; Makdissi, Fabiana Baroni Alves (Mastology, 2021)
Introduction: Nipple-Sparing Mastectomy (NSM) is increasingly indicated for therapeutic and prophylactic purposes due to better cosmetic results with nipple maintenance. Postoperative complications have not been compared among patients who have undergone simultaneous therapeutic and contralateral prophylactic NSM. The aim of the present study was to evaluate the incidence and risk factors for postoperative complications in bilateral/unilateral NSMs, and therapeutic and/or prophylactic NSMs. Methods: Retrospective study of patients who underwent NSM between 2007 and 2017 at A.C. Camargo Cancer Center. Results: Among 290 patients, 367 NSMs were performed, 64 simultaneous therapeutic and contralateral prophylactic NSM. The latter were associated with more postoperative complications (OR=3.42; p=0.002), mainly skin flap necrosis (OR=3.79; p=0.004), hematoma (OR=7.1; p=0.002), wound infection (OR=3.45; p=0.012), and nipple-areola complex (NAC) loss (OR=9.63; p=0.003). Of the 367 NSMs, 213 were unilateral NSMs, which were associated with lower rates of postoperative complications (OR=0.44; p=0.003), especially skin flap necrosis (OR=0.32; p=0.001), hematoma (OR=0.29; p=0.008), wound infection (OR=0.22; p=0.0001), and reoperation (OR=0.38; p=0.008). Obesity was related to more postoperative complications (OR=2.55; p=0.01), mainly hematoma (OR=3.54; p=0.016), reoperation (OR=2.68; p=0.023), and NAC loss (OR=3.54; p=0.016). Patients’ age (p=0.169), their smoking status (p=0.138), breast ptosis (0.189), previous chest radiotherapy (p 1), or previous breast surgery (p=0.338) were not related to higher chances of postoperative complications. Conclusions: Results suggest that performing therapeutic and contralateral prophylactic NSM as separated procedures may represent a good strategy for minimizing postoperative complications.